An Advanced Review on Resealed Erythrocytes - Begum, Gousia S.; D, Mustafa (Asian Journal of Pharmaceutical Research and Development, 2019)
Now a days there are numerous applications have been proposed for the use of resealed erythrocytes as carrier for drugs, enzyme replacement therapy etc. Until other carrier systems come of age, resealed erythrocytes technology will remain an active field for the further research. The use of resealed erythrocytes shows potential for a safe and effective delivery of various bioactive molecules for effective targeting. In coming future, erythrocyte based drug delivery system with their capability to afford controlled and site specific drug delivery have been developed for disease management. Erythrocyte carriers are “Nano devices in the field of Nanotechnology”. A large amount of valuable work is needed so as to utilize the potentials of erythrocytes in passive as well as active targeting of drugs in diseases like cancer. At present erythrocytes are most effective carriers in novel drug delivery systems considering their tremendous potential. Hence the present article is reviewed about method of drug loading, evaluation and applications of RSE.